Composição químico-bromatológica de feno de leucena em função do tempo de secagem e de armazenamento - Abot, Alfredo Raúl; Farias, Emerson Bispo; de Oliveira, Marcus Vinícius Morais; Torres, Francisco Eduardo; de Oliveira, Daniele Portela [UNESP]; Teodoro, Paulo Eduardo; Ribeiro, Larissa Pereira (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2015)
The leucaena is a leguminous that has high protein content and digestibility, can be supplied fresh or made into hay. The objective was to verify the influence of dehydration time of leaves and fine stems of leucaena and storage time on their chemical-bromatological characteristics. Cutting the fractions to be haymaking (leaves and stems smaller than one centimeter) was deposited on a plastic canvas for dehydration, being collected samples of the material at 0, 4th, 8th, 24th and 48th hours of dehydration to determine the levels of dry matter (DM), crude protein (CP), neutral detergent fiber (NDF), total carbohydrates (TC), not fibrous carbohydrates (NFC), ether extract (EE) and mineral matter (MM). The bales of hay were made using a manual baler and were kept stored in environment shaded, ventilated and protected of rain for 90 days. In that bales also were collected samples monthly to determine if occurred losses in nutritional quality. The dehydration time for 24 hours and storage for 30 days in water and allowed to dry to obtain the best chemical-bromatological composition of leucaena hay. The levels of CP, NDF, EE and MM decrease as function of drying time and storage both during the rainy as in the dry season, while the DM, TC and NFC increased due to these variables for both periods.
Chemical-bromatological compositon of leucaena hay as function of drying and storage times
Keywords: Fabaceae; Forage; Haymaking point; Leucaena leucocephala